Superfreakonomics : global cooling, patriotic prostitutes, and why suicide bombers should buy life insurance - Levitt, Steven D.; Dubner, Stephen J. (New York : William Morrow, 2009)
Whether investigating a solution to global warming or explaining why the price of oral sex has fallen so drastically, Levitt and Dubner mix smart thinking and great storytelling to show how people respond to incentives.
Includes bibliographical references and index.
Keywords: Economics -- Psychological aspects; Economics -- Sociological aspects